A systematic review of the literature on counselling and psychotherapy for the prevention of suicide: 2. Qualitative studies. Issue 1 (11th February 2014) - Winter, David; Bradshaw, Siobhan; Bunn, Frances; Wellsted, David
Abstract : Scope of review: The paper reports a meta‐synthesis of 13 qualitative studies of counselling and psychotherapy with people at risk of suicide. Publication time span: The studies considered were reported between 1997 and 2006. Publication origin: Seven studies were conducted in the UK, four in the USA, one in Canada, and one in Sweden. Findings: Themes in clients' and therapists' accounts of the process of counselling or psychotherapy were therapist qualities; therapy components; theoretical framework; and therapy techniques. Themes in their accounts of the effectiveness of counselling and psychotherapy were decrease in self‐destructive behaviour, and quality of life. Themes in clients' views of barriers to effective counselling or psychotherapy were therapist characteristics; therapy components; secrecy; and transferring to the real‐life situation. Secrecy was also identified as a barrier by therapists, as were responsibilities of the profession; training; and the nature of suicide and self‐harm. Facilitators of successful counselling and psychotherapy as identified by clients were responsibility; support; and teaching therapy skills to family members, the latter also being identified by therapists.